Oral self‐management of palbociclib (Ibrance®) using mobile technology protocol. (27th November 2020) - Mazzella Ebstein, Ann M.; Barton‐Burke, Margaret; Anthony, Venice; Smith, Andrea; Zhang, Zhigang; Robson, Mark
Abstract: Aim: This study will test the feasibility and effectiveness of mobile technology intervention on the patients' self‐management of oral anticancer medication. Secondary objectives include acceptability, the usefulness of text messages, and satisfaction by participants and nurses. Methods: This prospective two‐arm study will recruit patients ( N = 220) with metastatic breast cancer and initiating treatment with palbociclib (Ibrance ®). Allowing for attrition, patients will be randomized into the control ( N = 100) or intervention ( N = 100) group. Unidirectional text message reminders will be sent during the treatment cycle through a secure web application using the patient's smartphone. Self‐reported survey responses will be collected at three time points; at consent, end of treatment cycles, and the follow‐up clinic visit and include a demographic questionnaire, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire, Post study questionnaire and the R‐15 Patient Satisfaction Questionnaire. Nurses providing care for study patients will complete the Adaptation of Stamps Nurse Workload questionnaire. Data will be analysed an intent‐to‐treat analysis comparing the two arms. Study approval was obtained in December 2019 and funded in January 2020. Discussion: Smartphones are globally available and have text messaging capability which is increasingly being used as an intervention in healthcare studies. This study will test a low‐cost, nurse‐led intervention that enhances the patient's experience with oral anti‐cancer medications, improves access to care, reduces costs, and improves the satisfaction of nurses caring for oncology patients. Impact: Despite the ease of administering oral anti‐cancer medications, oncology patients maynot take them as prescribed and consequently, these factors affect patient outcomes and disease control. Given the importance of taking oral anti‐cancer medications and the difficulties patients experience in achieving it, the effective use of mobile technology interventions can actively engage patients in their care and improve medication self‐management of anticancer treatment regimens. 摘要: 目的: 本项研究旨在验证移动技术干预对患者口服抗癌药物自我管理的可行性和有效性。次要目的包括可接受性, 短信的有用性, 以及参与者和护士的满意度。 方法: 这项前瞻性双臂研究将招募转移性乳腺癌患者 ( N=220 ), 并开始使用帕博西尼(爱博新®) 进行治疗。考虑到损耗, 患者将被随机分为对照组 ( N=100 ) 或干预组 ( N=100 ) 。在治疗周期内, 将使用患者智能手机的安全web应用程序发送单向短信提醒。将在三个时间点收集自我报告的调查结果: 同意时、治疗周期结束时和随访门诊就诊, 包括人口统计问卷、欧洲癌症研究与治疗组织生活质量调查问卷, 研究后调查问卷和R‐15患者满意度调查问卷。护理研究病人的护士将完成护士工作量调查问卷的改编。将分析数据, 并对两组数据进行意向—治疗分析比较。该项研究于2019年12月获得批准, 于2020年1月获得资助。 讨论: 智能手机在全球范围内均可使用, 并具有短信功能, 因此其越来越多地被用作医疗保健研究的干预手段。此项研究将测试一种低成本的、护士主导的干预措施, 以提高患者口服抗癌药物的经验、改善获得护理的机会、降低成本, 以及提高护理人员对肿瘤患者的满意度。 影响: 尽管口服抗癌药物很容易服用, 但肿瘤患者可能不按医嘱服用, 因此, 这些因素会影响患者恢复结果和疾病控制。考虑到口服抗癌药物的重要性以及患者在服用过程中遇到的困难, 有效地使用移动技术干预可以有效地让患者参与到他们的护理中, 并改善抗癌治疗方案的药物自我管理。